Relative impact of spider predation and cover crop on population dynamics of Erythroneura variabilis in a raisin grape vineyard - Hanna, R.; Zalom, F.; Roltsch, W. (Wiley, 2003)
Experimental and correlative evidence has steadily mounted over the past 30 years implicating spiders in the suppression of insect herbivore pests in crop fields. A large body of evidence has also shown that increasing agroecosystem vegetation diversity often influences the abundance of herbivores and their natural enemies. In previous experiments, the abundance of several species of spiders on grapevines in a raisin grape vineyard was twofold enhanced in vineyard plots vegetationally diversified with a cover crop. A concomitant reduction in the abundance of the leafhopper pest Erythroneura variabilis Beamer was observed on grapevines in the diversified plots, but a causal relationship was not established. In the present study, we simultaneously manipulated spider densities (in open-vine spider exclusion and vine-shoot enclosures) and ground cover to determine their relative impact on E. variabilis population dynamics. Open-vine spider exclusion resulted in an average 35% increase in the density of E. variabilis the greatest effect with occurring during the first and second leafhopper generations. The negative impact of spiders on E. variabilis densities was corroborated with vine-shoot enclosure experiments. Under the conditions of the present study, the cover crop per se did not affect the dynamics of E. variabilis populations on grapevines, despite a 1.6-fold increase in spider densities on vines in cover crop plots, compared with vines in bare ground plots, probably due to insufficient spider enhancement and low overall E. variabilis abundance during the summer months. The cover crop had little effect on vine macronutrient status (and presumably vine water status). While this study provided further support for the hypothesis that vegetation diversity can enhance spider abundance, this enhancement does not always lead to lower pest densities, thus underscoring the complexity and variability that exists in interactions involving cover crop, spiders, and crop plants and their herbivore pests.